2012
DOI: 10.4236/ajcc.2012.14019
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical Characteristics of Groundwater for Domestic and Irrigation Purposes in Dwarakeswar Watershed Area, India

Abstract: The Hydrochemical study was carried out in Dwarakeswar watershed area, Bankura and Purulia districts, West Bengal, India, with an objective of understanding the suitability of local groundwater quality for domestic and irrigation purposes. Groundwater samples have been collected from different villages within Dwarakeswar watershed area. The samples have been analysed to determine physical parameters like pH, EC, TDS and Hardness, the chemical parameters like Na, K, Ca, Fe, HCO 3 , SO 4 and Cl. From the analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 6 publications
1
18
1
Order By: Relevance
“…e permissible limit for anions HCO 3 − and Cl − is 250 mg L −1 [30,31]. e values of HCO 3 − and Cl − in the groundwater samples varied from 29.2 to 372.0 mg L −1 and 8.2 to 252.4 mg L −1 , respectively ( Table 2). e results on major anions revealed that 64% water samples as per the limit of HCO 3 − and 98% as per the limit of Cl − were observed to be fit for irrigation purpose.…”
Section: Water Quality Based On the Absolute Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…e permissible limit for anions HCO 3 − and Cl − is 250 mg L −1 [30,31]. e values of HCO 3 − and Cl − in the groundwater samples varied from 29.2 to 372.0 mg L −1 and 8.2 to 252.4 mg L −1 , respectively ( Table 2). e results on major anions revealed that 64% water samples as per the limit of HCO 3 − and 98% as per the limit of Cl − were observed to be fit for irrigation purpose.…”
Section: Water Quality Based On the Absolute Ionsmentioning
confidence: 99%
“…According to a national sample survey, 56% households get drinking water from hand pump or tube well, 14% from open well, and 25% based on piped water [2]. Groundwater gets contaminated with a variety of pollutants such as domestic, agriculture, and industrial due to utilization of fertilizers, pesticides, and other chemical products [3]. e groundwater quality assessment based on different agriculture indices has been studied in different parts of world [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…into the groundwater making the groundwater harder. Water with higher hardness are not suitable for domestic and industrial purposes (Sarath Prasanth et al 2012); (Gopinath et al 2015); (Tahlawi et al 2016); (Nag and Lahiri 2012). The total hardness for water samples was determined using the expression (Todd 1980 The total hardness of the water samples ranges from 5 to 353 and 13 to 387 mg/L in both the seasons (Table 4; Table 1; Fig.…”
Section: Total Hardnessmentioning
confidence: 99%
“…are the processes governing hydrochemistry (Hem 1985). The fertilizers, pesticides and other chemical products used for agriculture also affect the groundwater quality (Nag and Lahiri 2012). Several authors have reported about the quality of groundwater worldwide (Batayneh et al 2014;Senthilkumar et al 2014;Kazemi and Mohammadi 2012;Kumar et al 2015;Krishna Kumar et al 2011;Nwankwoala et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…If the concentration of any parameter is above the prescribed limit (according to WHO and BIS specifications) there can be serious health issues. Several workers have assessed the groundwater quality and its suitability for drinking and irrigation purposes (Al-Futaisi et al 2007;Jalali 2006;Pritchard et al 2008;Rivers et al 1996;Nag and Lahiri 2012;Nag and Ghosh 2013;Nag 2014;Nag and Das 2017;Tiwari 2011). Aghazadeh and Mogaddam (2010) assessed the groundwater quality and its suitability in the Oshnavieh area, Iran based on physical and chemical parameters.…”
Section: Introductionmentioning
confidence: 99%